Respuesta :
Answer:
-3x+5(x+3)=4+3x+7(x-6)
We move all terms to the left:
-3x+5(x+3)-(4+3x+7(x-6))=0
We multiply parentheses
-3x+5x-(4+3x+7(x-6))+15=0
We calculate terms in parentheses: -(4+3x+7(x-6)), so:
4+3x+7(x-6)
determiningTheFunctionDomain
3x+7(x-6)+4
We multiply parentheses
3x+7x-42+4
We add all the numbers together, and all the variables
10x-38
Back to the equation:
-(10x-38)
We add all the numbers together, and all the variables
2x-(10x-38)+15=0
We get rid of parentheses
2x-10x+38+15=0
We add all the numbers together, and all the variables
-8x+53=0
We move all terms containing x to the left, all other terms to the right
-8x=-53
x=-53/-8
-3x+5(x+3)=4+3x+7(x-6)
We move all terms to the left:
-3x+5(x+3)-(4+3x+7(x-6))=0
We multiply parentheses
-3x+5x-(4+3x+7(x-6))+15=0
We calculate terms in parentheses: -(4+3x+7(x-6)), so:
4+3x+7(x-6)
determiningTheFunctionDomain
3x+7(x-6)+4
We multiply parentheses
3x+7x-42+4
We add all the numbers together, and all the variables
10x-38
Back to the equation:
-(10x-38)
We add all the numbers together, and all the variables
2x-(10x-38)+15=0
We get rid of parentheses
2x-10x+38+15=0
We add all the numbers together, and all the variables
-8x+53=0
We move all terms containing x to the left, all other terms to the right
-8x=-53
x=-53/-8
Answer:
2x+15=11x-38
Step-by-step explanation:
-3x+5(x+3)=4+3x+7(x-6) (first do the parentheses)
-3x+5x+15=4+3x+7x-42 (then add the common terms)
2x+15=11x-38